1989
DOI: 10.1007/bf02385430
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of silicon nitride in a wet atmosphere

Abstract: The effect of water vapour on oxidation was studied with hot-pressed silicon nitride containing both yttria and alumina as sintering aids in wet air flow with 10, 20, 30, and 40vo1% H20 at 1300°C for 10Oh. The oxidation kinetics were determined in a wet air flow with 20vo1% H20 and in a dry air flow at 1300 °C for oxidation times up to 360h. The water vapour in the atmosphere slightly influenced the oxidation and accelerated the reaction, and the weight gained on oxidation in a wet atmosphere had an increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The results from the present study reveal two significant features: (i) the weight loss rates follow the predicted square root dependence on vapor velocity, and (ii) there is a threshold velocity below which the volatilization is negligible. Reports at low gas velocities (<0.44 cm/s) have shown that specimens show only a weight gain, 15,18–21 which is in agreement with the threshold velocity concept.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results from the present study reveal two significant features: (i) the weight loss rates follow the predicted square root dependence on vapor velocity, and (ii) there is a threshold velocity below which the volatilization is negligible. Reports at low gas velocities (<0.44 cm/s) have shown that specimens show only a weight gain, 15,18–21 which is in agreement with the threshold velocity concept.…”
Section: Discussionsupporting
confidence: 84%
“…Analysis of the data indicates the presence of a threshold velocity for volatilization. There are some oxidation studies reported in the literature at very low gas velocities of <0.5 cm/s 15,18–21 and they report only a weight gain, supporting the threshold velocity concept.…”
Section: Discussionmentioning
confidence: 72%
“…Except for specimen ''B,'' tested for only 10 h at 14501C, the compact band of Yb 2 Si 2 O 7 around the grounded side of the resistors was observed in all sections at 5 mm back from the tip (Figs. 7,9,12,13,15). The effect of test duration at the same temperature (15001C) is shown in Fig.…”
Section: Wwwceramicsorg/actmentioning
confidence: 96%
“…The intergranular oxynitride glassy phase in Si 3 N 4 provides a continuous transport medium between the surface silicate scale and the Si 3 N 4 bulk, by the outward diffusion of R 3+ cations and inward diffusion of oxygen 1,2 . While oxidation of Si 3 N 4 ‐based ceramics in dry air and oxygen was extensively studied, 1–5 it is known that silicon nitride oxidizes up to an order of magnitude faster in wet than in dry oxygen and the mechanism changes from parabolic to paralinear 6–12 . Additionally, the swings of oxidizing/reducing conditions in combustion environments can affect the stability of the silicate film on the component's surface; numerous studies have focused on the corrosion of silicon‐based ceramics under these complex combustion conditions 13–20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation